Industrial relations in European hypermarkets: Home and host country influences. (September 2014) - Geppert, Mike; Williams, Karen; Wortmann, Michael; Czarzasty, Jan; Kağnicioğlu, Deniz; Köhler, Holm-Detlev; Royle, Tony; Rückert, Yvonne; Uçkan, Banu
In this article we examine the industrial relations practices of three large European food retailers when they transfer the hypermarket format to other countries. We ask, first, how industrial relations in hypermarkets differ from those in other food retailing outlets. Second, we examine how far the approach characteristic of each company's country-of-origin (Germany, France and the UK) shapes the practices adopted elsewhere. Third, we ask how they respond to the specific industrial relations systems of each host country (Turkey, Poland, Ireland and Spain).